2008
DOI: 10.1086/524935
|View full text |Cite
|
Sign up to set email alerts
|

Warm Dust in the Terrestrial Planet Zone of a Sun‐like Pleiades Star: Collisions between Planetary Embryos?

Abstract: Only a few solar-type main-sequence stars are known to be orbited by warm dust particles; the most extreme is the G0 field star BD +20 307 that emits $4% of its energy at mid-infrared wavelengths. We report the identification of a similarly dusty star HD 23514, an F6-type member of the Pleiades. A strong mid-IR silicate emission feature indicates the presence of small warm dust particles, but with the primary flux density peak at the nonstandard wavelength of $9 m. The existence of so much dust within an AU or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 48 publications
4
92
1
Order By: Relevance
“…Early searches for 12 µm emission from dust around nearby stars with IRAS were not particularly successful (Aumann and Probst 1991), though several good candidates were rediscovered in the last decade and followed up with higher resolution instruments to confirm the emission was associated with the star and to characterise its spectrum (e.g., Rhee et al 2008;Melis et al 2010). These hot excesses were picked out on a case-by-case basis, and interpreted again within the context of terrestrial planet formation, based on the fact that the stars with bright emission were predominantly found around < 100 Myr stars.…”
Section: Photometric Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early searches for 12 µm emission from dust around nearby stars with IRAS were not particularly successful (Aumann and Probst 1991), though several good candidates were rediscovered in the last decade and followed up with higher resolution instruments to confirm the emission was associated with the star and to characterise its spectrum (e.g., Rhee et al 2008;Melis et al 2010). These hot excesses were picked out on a case-by-case basis, and interpreted again within the context of terrestrial planet formation, based on the fact that the stars with bright emission were predominantly found around < 100 Myr stars.…”
Section: Photometric Fluxesmentioning
confidence: 99%
“…There are more uncertainties about the exact formation mechanism of the outer Solar System (Goldreich et al 2004;Helled and Bodenheimer 2014), but there are several lines of evidence to suggest that giant impacts were also a feature of the more distant reaches of the Solar System (e.g., Safronov 1972;Canup 2005). There is also growing evidence for giant impacts having occurred recently in some extrasolar planetary systems, from observations of what could be impact-generated debris (Song et al 2005;Rhee et al 2008). Stars with anomalously high levels of dust in their regions that would be analogous to the location of terrestrial planets in the inner Solar System are often interpreted within the context of terrestrial planet formation (e.g., Lisse et al 2008;Melis et al 2010), particularly if they are at an age at which planet formation models predict such giant impacts to be taking place (i.e., 100 Myr).…”
Section: Introductionmentioning
confidence: 99%
“…Thus the infrared spectrum of BD +20 307 likely is our best current measure of the spectrum of dust derived from extrasolar rocky parent bodies. Rhee et al (2008) have reported an infrared excess around HD 23514, an F-type main-sequence star in the Pleiades, which, like BD +20 307, also reprocesses more than 1% of the host star's luminosity. However, the silicate emission from HD 23514 peaks near 9 µm, and the feature is very non-standard.…”
Section: Observations and Datamentioning
confidence: 99%
“…Planet formation models and radiometric dating suggest that terrestrial planets reach their final mass by $10Y30 Myr (Wetherill & Stewart 1993;Yin et al 2002;Kenyon & Bromley 2006). Terrestrial planet formation produces debris emission observable at %5Y10 m. Mid-IR Spitzer observations reveal terrestrial zone dust emission around many 13 Myr old stars in the massive double cluster, h and Persei, and around several stars in other P40 Myr old clusters/associations, including the Sco-Cen association, NGC 2547, and the Pic moving group ( Zuckerman & Song 2004;Chen et al 2005Chen et al , 2006Currie et al 2007b;Rhee et al 2007a;Gorlova et al 2007;Currie et al 2008a;Lisse et al 2008). 3 Observations of many warm, IRAC-excess stars in h and Per point to a spectral type/stellar massYdependent evolution of terrestrial zone dust, which suggests that the terrestrial planet formation process runs to completion faster for high-mass stars than it does for intermediate-mass stars (Currie et al 2007c;Currie 2008).…”
Section: Introductionmentioning
confidence: 99%